Vibrational Spectroscopy and Density Functional Theory Calculations of Poly- D -Mannuronate and Heteropolymeric Fractions from Sodium Alginate - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Cardenas-Jiron, G; Leal-Rifo, D (2011)
The tetrasaccharide of 1 ? 4?-D-mannopyranuronate (MM) and the alternating tetrasaccharide of 1 ? 4 b-D-mannopyranuronate and 1 ? 4?-L-gulopyranuronate (MG) were analyzed based on density functional theory (DFT) by employing the Gaussian 03 W package. The molecular geometries were fully optimized by using the Becke s three-parameter hybrid exchange functional combined with Lee-Yang-Parr correlation functional (B3LYP) and using a 6-31G(d,p) basis set. The calculated IR spectrum of MM presents a band at 1093 cm-1 for Ci- C stretching vibration, which is in good agreement with the experimental observation (1096 cm-1) for the polymannuronate fraction obtained by partial hydrolysis of sodium alginate extracted from the hybrid brown seaweed Lessonia-Macrocystis. The calculated value at 826 cm -1for MM is in close agreement with the experimental value and confirms that this band is characteristic of polymannuronate blocks. Most of the bands in the IR spectrum are also present in the observed Raman spectrum of the polymannuronate fraction. The experimental IR spectrum of heteropolymeric fraction obtained by partial hydrolysis of sodium alginate shows absorbances similar to those calculated for the model tetrasaccharide (MG). Surface-enhanced Raman scattering (SERS) allows differentiation between the homopolymeric and heteropolymeric fractions of sodium alginate. The SERS spectrum of the heteropolymeric fraction shows an enhanced signal at 731 cm-1which is present in the calculated Raman spectrum of the tetrasaccharide MG at 729 cm-1. This band is assigned to the ring-breathing deformation of the ?-D-mannopyranuronate and ?-L-gulopyranuronate residues. Polymannuronate and heteropolymeric fractions from sodium alginate were analyzed by IR, Raman and SERS techniques. Assignments of the vibrational modes were performed using the calculated spectra of the model mannuronate and mannuronate-guluronate tetrasaccharides. Copyright © 2010 John Wiley & Sons, Ltd.